FORMULASI DAN UJI ANTIBAKTERI SPRAY HAND SANITIZER DARI EKSTRAK DAUN PILADANG (Plectransthus Scutellaroides (L) R.Br) TERHADAP Staphylococcus aureus - Dewi, Hasna (Journal of Pharmacy Tiara Bunda, 2022)
Piladang leaf (Plectranthus scutellaroides (L) R.Br) is a plant that has antibacterial activity, one of which is Staphylococcus aureus, so it can be used as an active ingredient in spray hand sanitizer or hand antiseptic spray. This study aims to formulate piladang leaf extract in the form of spray hand sanitizer and to test its antibacterial activity against Staphylococcus aureus using agar diffusion method. In this research, 3 spray hand sanitizer formulas were made with variations in the concentration of piladang leaf extract 3.5%; 7% and 10.5%. Then performed a physical stability test with test parameters including organoleptic, viscosity, homogeneity, pH, stability, irritation test and dry time test. The results showed that based on physical stability tests it was found that organoleptically, viscosity, homogeneity, pH and stability for the three formulas was stable during storage, then based on the antibacterial spray hand sanitizer test against Staphylococcus aureus, it was found that the concentration of piladang leaf extract affected the inhibition of growth of Staphylococcus aureus by showing inhibition of 15.18 mm for a concentration of 3.5%; 17.2 mm for a concentration of 7% and 22.08 mm for a concentration of 10.5%.